PENGARUH GOOD CORPORATE GOVERNANCE DAN LEVERAGE TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BEI - Ramadeni, Fesi; Dewi, Aminar Sutra (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2023)
This research aims to determine and analyze the influence of Good Corporate Governance and Leverage on financial performance in banking companies listed on the Indonesia Stock Exchange (BEI). The method used is the panel data regression method, and uses the classic assumption test to test classical deviations that usually occur, including the normality test. This panel data regression analysis was carried out with the help of the Eviews computer program. The sample used in this research was 35 companies in banking companies that were missing on the IDX with an observation period of 5 years, namely from 2016 to 2020. Based on the research results, the board of commissioners, board of directors and audit committee had a positive and significant effect on financial performance, while Leverage has no significant effect on financial performance.